Sistem Informasi Desa Wisata Bobung Sentra Kerajinan Tangan Berbasis Web - Carissa Liora; Wasino Wasino; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Bobung Tourism Village is located in Patuk District, Gunung Kidul Regency, known as Handicraft Center. To find more information and detail about Bobung Tourism Village is clearly difficult because the promotion and socialization to the surrounding community is still lacking. Therefore will be made Bobung Tourism Village Information System Handicraft center Based web. The purpose of making a website-based application for Bobung Tourism Village is to make the promotion more effective and efficient in displaying and disseminating information about the arts and culture in Bobung Tourism Village also other activities offered by the people in Bobung Village Tourism so it became better known to the public.The methods used for data collection are literature study and documentation. The research method used SDLC (System Developtment Life Cycle). PHP is the programming language used for this web based application and also use MySQL as for the database. This website can help provide information about Bobung through website include the tourist attraction, tour packages, studio, handicrafts and tourism news about Bobung Tourism Village.